Case Report: Galvanic Vestibular Stimulation in the Chronic Spinal Cord Injury Patient - Nascimento, Tais Nunes; Boffino, Catarina Costa (Frontiers in Rehabilitation Sciences, 2022)
The traumatic spinal cord injury can generate sequels with high clinical severity and dysfunction and limitations of irreversible character. Current studies seek to reverse the sequelae and gain functionality in these individuals. Galvanic vestibular stimulation (GVS) has shown to be beneficial in spinal cord function as an evaluation correlated to functionality and for stimulation with physiological and functional characteristics in disease and healthy people. The present study observed the effects of Noise Galvanic Vestibular Stimulation in a patient with chronic spinal cord injury with tetraplegia on postural and trunk control. The evaluations were the Functional Independence Measure (FIM), the American Spinal Injury Association (ASIA) evaluation, and the Clinical Posturography, using force platform to assess postural balance, in the sitting position, through Sensory Organization and Functional Reach Tests. Ten sessions of Noise Galvanic Vestibular Stimulation associated with customized vestibular and neurofunctional rehabilitation were performed. The effects observed were increments in all assessments and tests that include modifications in functional independence, motor and sensory levels, change in disability grade from A (complete) to C (incomplete), and improvements in postural balance and trunk control. The phenomenon of stochastic resonance has shown benefits in postural control in people without vestibular lesions and we could observe some of these phenomena in our patients. We emphasize the need for evaluation with larger populations to observe the phenomena and effects in this group of patients and potential benefits and limitations.